2022
DOI: 10.1177/03000605221134466
|View full text |Cite
|
Sign up to set email alerts
|

Mental health consequences of COVID-19 suppression strategies in Victoria, Australia: a narrative review

Abstract: The COVID-19 pandemic has imposed significant mental health burdens upon the general population worldwide, either directly owing to the disease or indirectly through aggressive public health measures to control spread of the virus that causes COVID-19. In this narrative review, we used a systematic approach to summarize the impact of restrictive lockdown measures on the general mental health of people living in Victoria, Australia during 2020 and to identify the groups with an increased risk of adverse mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(117 reference statements)
1
3
0
Order By: Relevance
“…While participants did not report any differences in the quantitative assessment of impact of the pandemic on mental health, qualitative feedback demonstrated increased psychological distress and isolation in some participants. The comments are consistent with studies which found significant increases in clinical depression and anxiety in the general Victorian population during the prolonged restrictions [ 8 , 23 ], likely due to the cumulative impacts of lockdown on population mental health. Similarly, adults with type 2 diabetes mellitus in Victoria have also self-reported negative impacts of the pandemic restrictions on emotional wellbeing and leisure activities, despite the study finding no increased anxiety or depressive symptoms compared to pre-COVID-19 levels [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While participants did not report any differences in the quantitative assessment of impact of the pandemic on mental health, qualitative feedback demonstrated increased psychological distress and isolation in some participants. The comments are consistent with studies which found significant increases in clinical depression and anxiety in the general Victorian population during the prolonged restrictions [ 8 , 23 ], likely due to the cumulative impacts of lockdown on population mental health. Similarly, adults with type 2 diabetes mellitus in Victoria have also self-reported negative impacts of the pandemic restrictions on emotional wellbeing and leisure activities, despite the study finding no increased anxiety or depressive symptoms compared to pre-COVID-19 levels [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, an observational longitudinal study conducted in France and Switzerland found that walking and moderate physical activity increased during the pandemic compared to pre-pandemic levels, albeit sedentary behaviour also increased [ 21 ]. In Australia, increased alcohol-use associated with social isolation and pandemic lockdowns has been reported, but these studies have focused on the general population rather than CKD patients [ 22 , 23 ]. Further research should focus on how the pandemic has impacted specific areas of CKD patients’ physical health, and how patients can adapt their lifestyle strategies to suit the evolving pandemic context.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the delayed and minimal presence of COVID-19 community transmission and associated restrictions/lockdowns in Tasmania, there were increased escalations and prevalence of mental health concerns. The wellbeing of Tasmanians is heavily influenced by events on the mainland, with mental health trends aligned with other states that experienced strict and prolonged lockdowns, including Victoria and New South Wales (Jiang et al 2022). This is likely due to the impact of social media and other news sources, which saturated COVID-19 content over this time (Price et al 2022).…”
Section: Discussionmentioning
confidence: 95%
“…For example, over one-quarter of undergraduates have depression at any given time [ 1 , 2 ] and the peak onset of mental illness and initial diagnoses is found in the age group typically undertaking higher education (i.e., 18–25 years of age; [ 3 ]). In recent years, exacerbated by the COVID-19 pandemic, poor mental health, including the prevalence of disorders and the severity of mental health symptoms, within higher education settings continues to be commonplace [ 1 , 4 , 5 ]. Students frequently choose to undertake a university course based on their personal interests, often influenced by previous life experiences, e.g., [ 6 ].…”
Section: Introductionmentioning
confidence: 99%